Synthèse, étude et validation structurale d'un triple bis-molybdate en couches, Ag0.60Na0.40Fe(MoO4)2 lié à yavapaiite - Amira Souilem; Mohamed Faouzi Zid (Acta Crystallographica Section E: Crystallographic Communications, 2016)
The title compound, Ag0.60Na0.40Fe(MoO4)2 {silver sodium iron(III) bis[molybdate(VI)]}, was synthesized by a solid-state reaction. The structure is built up from FeO6 octahedra and MoO4 tetrahedra sharing corners to form a two-dimensional framework parallel to the (001) plane. The occupationally disordered (Ag/Na)+ cations are located in the interlayer space. These [Fe(MoO4)2−]n layers are similar to those in the isotypic yavapaiite-related structure of NaFe(MoO4)2. All atoms are on general positions except for Fe (site symmetry -1) and Ag/Na (site symmetry 2). The Ag/Na occupancies of the latter site were refined to 0.597 (4):0.403 (5). The title structure is compared to similar structures.